2015
DOI: 10.1063/1.4919221
|View full text |Cite
|
Sign up to set email alerts
|

Rubber friction on road surfaces: Experiment and theory for low sliding speeds

Abstract: Effect of fluorocarbon self-assembled monolayer films on sidewall adhesion and friction of surface micromachines with impacting and sliding contact interfaces J. Appl. Phys. 113, 224505 (2013) We study rubber friction for tire tread compounds on asphalt road surfaces. The road surface topographies are measured using a stylus instrument and atomic force microscopy, and the surface roughness power spectra are calculated. The rubber viscoelastic modulus mastercurves are obtained from dynamic mechanical analysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 45 publications
2
95
0
Order By: Relevance
“…Persson's theory, on the other hand, in the latest forms (Lorenz et al [8]), seems to have a surprisingly simple criterion for truncation wavenumber q 1 = 2π/λ min : it is defined where the rms slope reaches H rms (q 1 ) = 1.3 (1) although other authors (Carbone & Putignano [9]) are more cautious about many possible choices to the truncation cutoff, e.g., small dirt particles or rubber wear particles. However, more recently, both Klüppel and co-authors [10][11][12] and Persson and Volokitin [13] seem to attribute a lot more importance to the adhesive term than the viscoelastic one.…”
Section: Introductionmentioning
confidence: 99%
“…Persson's theory, on the other hand, in the latest forms (Lorenz et al [8]), seems to have a surprisingly simple criterion for truncation wavenumber q 1 = 2π/λ min : it is defined where the rms slope reaches H rms (q 1 ) = 1.3 (1) although other authors (Carbone & Putignano [9]) are more cautious about many possible choices to the truncation cutoff, e.g., small dirt particles or rubber wear particles. However, more recently, both Klüppel and co-authors [10][11][12] and Persson and Volokitin [13] seem to attribute a lot more importance to the adhesive term than the viscoelastic one.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the currently available data, it may not be possible to associate the overall difference between the frictional behaviour of the two samples with any of the contributions from the hysteresis or the frictional shear stresses (adhesion). This frictional shear stresses is well discussed in the latest work of Lorenz et al (2015). What is evident to us is the higher wearing rate of the rubber on the asphalt specimen compared with its replica, which is due to the micro-asperities present on the surface of the asphalt slab and not on the prints.…”
Section: Frictional Behaviour Of the Prints 331 Asphalt Specimen Vmentioning
confidence: 83%
“…In tyre-road friction, the complex nature of the rubber on the one hand and the multiscale roughness of the road on the other make the friction problem even more challenging to tackle. Despite the large number of recent numerical and analytical studies on the fundamental theory behind rubber friction (Carbone & Putignano, 2013;Klüppel & Heinrich, 2000;Lorenz, Oh, Nam, Jeon, & Persson, 2015;Persson, 2001Persson, , 2006Scaraggi & Persson, 2015) a theory that can fully explain the experiments has not yet been derived. Hence, it is essential that the experimental work on rubber friction is first arranged in simpler cases and under controllable conditions.…”
Section: Introductionmentioning
confidence: 97%
“…The stick-slip events should manifest itself in the power spectrum of the block velocity or perhaps in the acoustic power spectrum, so studying these quantities should be one way to test the hypothesis presented above. Rubber friction: role of frictional heating There are two contributions to rubber friction, one from the viscoelastic deformations of the rubber by the road asperities [24,33], and another from shearing the area of real contact [31,32], the latter is usually referred to as the adhesive contribution [34]. Earlier studies have shown that at room temperature the maximum in the adhesive contribution is located below the typical slip velocities in tire applications (1 − 10 m/s), while the maximum in the viscoelastic contribution may be located above typical sliding speeds as is indicated in Fig.…”
Section: Friction On Non-randomly Rough Surfacesmentioning
confidence: 99%